2021
DOI: 10.1007/s10340-021-01360-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasma irradiation on Tribolium castaneum

Abstract: Radio frequency plasma (RFP) could provide reliable, compact, cost-effective irradiation applications against insect pests of stored food and feed products. Sensitivity of red flour beetle Tribolium castaneum to RFP has been investigated using an irradiation applicator system with the two types of inert gases, argon (Ar) and helium (He), at 100 W for five exposure time levels of 0, 20, 40, 60 and 90 s, respectively. We demonstrated that He RFP was more efficient against T. castaneum than Ar RFP. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
3
6
0
1
Order By: Relevance
“…Our results showed that the survival rates of plasma-exposed PRM depended significantly on the exposure time and, moreover, may be time-delayed. These results correspond to the findings of Donohue et al ( 2006 ) and Sayed et al ( 2021 ) that the mortality rate of plasma-treated insects depends not only on the duration of CAPP exposure but also in the post-plasma exposure period. In our study, PRM demonstrated significant differences in survival rates with respect to the utilized exposure duration.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results showed that the survival rates of plasma-exposed PRM depended significantly on the exposure time and, moreover, may be time-delayed. These results correspond to the findings of Donohue et al ( 2006 ) and Sayed et al ( 2021 ) that the mortality rate of plasma-treated insects depends not only on the duration of CAPP exposure but also in the post-plasma exposure period. In our study, PRM demonstrated significant differences in survival rates with respect to the utilized exposure duration.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, in female PRM adults the lethal effect of CAPP occurred time-delayed, so that complete cumulative mortality was achieved later on. Similarly, it was described by Sayed et al ( 2021 ) that adult red flour beetles are in turn more tolerant to indirect effects such as reactive oxygen species. These could presumably damage the cells, leading to a time-delayed lethal effect of CAPP in insects (Sayed et al 2021 ).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations